Stimulus-response time to invasive blood pressure alarms: implications for the safety of critical-care patients - Adele Kuckartz Pergher; Roberto Carlos Lyra da Silva
Observational, descriptive, exploratory, case study with the objective of measuring the stimulus-response time of the team to alarms monitoring invasive blood pressure (IBP) and analyzing the implications of this time for the safety of the patient. From January to March 2013, 60 hours of structured observation were conducted with registration of the alarms activated by IBP monitors in an adult ICU at a military hospital in the city of Rio de Janeiro. 76 IBP alarms were recorded (1.26 alarms/hour), 21 of which (28%) were attended to and 55 (72%) considered as fatigued. The average response time to the alarms was 2 min. 45 sec. The deficit in human resource and physical layout were factors determining the delay in response to the alarms. The increase in response times to these alarms may compromise the safety of patients with hemodynamic instability, especially in situations such as shock and the use of vasoactive drugs.